Assisted Listening Using a Headset - Gamper, Hannes; Franck, A.; Rämö, J.; Savioja, L.; Välimäki, V. (IEEE Signal Processing Magazine, 2015)
Historically, headphones have mainly been used for analytic listening in music production and in homes. During the last decade, with the boom of dedicated music players and mobile phones, the everyday use of light headphones has become highly popular. Current headphones are also paving the way for more sophisticated assisted listening devices. Today, active noise control (ANC), equalization techniques, and a hear-through function are already a standard part of many headphones that people commonly use while traveling. It is not difficult to predict that, in the near future, a headset will be a "hearing aid for those with normal hearing," which can improve listening conditions for example in a noisy environment.
(accepted for publication)